Arduino Uno Programming Training for Senior High School in the City of Tasikmalaya - Aceng Sambas; Gugun Gundara; Mujiarto Mujiarto; Volodymyr Rusyn; Aan Andriana; Faisal Abdul Aziz (Research Collaboration Community (RCC), 2022)
This study aims to program basic Arduino UNO. First, we create an Arduino simulation circuit to turn on the Light Emitting Diode (LED) in the Proteus software. Next, make Arduino programming for the running LED. Finally, enter the Arduino program into the Arduino circuit on Proteus. This Arduino UNO programming training will be introduced to teachers in online training activities. With this training, it is hoped that teachers will be able to increase innovation and creativity in the subjects taught,